40.6k views
0 votes
The first three steps in determining the solution set of the system of equations, y = –x2 – 2x + 8 and y = 2x + 11, algebraically are shown in the table

1 Answer

2 votes
First step
Using substitution you can fill 2x + 11 in for the y part of the first equation
This will look like: 2x + 11 = -x^2 -2x + 8

Second step
Now we need to solve for the variable by combining like terms you can start by adding x^2 + 2x -8 to both sides
You get 0 = x^2 +4x +3

Third step
Factor
(X+3)(x+1)=0

If you need the y values you can fill in x= -3 to the second equation y= 2(-3) + 11 and y=5
First point is (-3,5)

The other point is found by filling x=-1 into the second equation: y= 2(-1) +11 and y = 9
Second point is (-1,9)
User Joseph Duffy
by
5.1k points